2017
DOI: 10.1088/0256-307x/34/10/108102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Micro and Nano Size WO3/E44 Epoxy Composite as Gamma Radiation Shielding Using MCNP and Experiment

Abstract: The radiation shielding characteristics of 50 wt% WO3/E44 epoxy composite in various gamma energies from 80 keV to 1.33 MeV are investigated via the MCNP code. Thus two scales are considered for WO3 filler particles: micro and nano with sizes of and 50 nm, respectively. The simulation results show that WO3 nano particles exhibit a larger increase in linear attenuation coefficient in comparison with micro size particles. Finally, validation of simulation results with the published experimental data shows a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…Moreover, some studies have been carried out on the effect of shielding materials grain size on linear attenuation coefficients. It is widely believed that nano-sized particles are able to disperse more uniformly within the matrix with fewer agglomerations when compared with micro-sized particles, thus improving the radiation attenuation ability of the materials [49]. As mentioned before, the particle size of the natural bentonite clay was measured to be 59.79 nm.…”
Section: Linear Attenuation Coefficientmentioning
confidence: 86%
“…Moreover, some studies have been carried out on the effect of shielding materials grain size on linear attenuation coefficients. It is widely believed that nano-sized particles are able to disperse more uniformly within the matrix with fewer agglomerations when compared with micro-sized particles, thus improving the radiation attenuation ability of the materials [49]. As mentioned before, the particle size of the natural bentonite clay was measured to be 59.79 nm.…”
Section: Linear Attenuation Coefficientmentioning
confidence: 86%
“…Similar studies showed that the WO 3 filler with a weight percentage of 50 wt% had an interesting performance in attenuation/absorption of high-energy gamma photons [8,11]. Therefore, similar weight percentage was selected (including 50% PVA and 50% WO 3 with 2.04 g/cm 3 density), and the Monte Carlo N-particle Transport Code (MCNPX 2.6.0) was used to carry out the simulation, which will be explained as follow.…”
Section: Methodsmentioning
confidence: 94%
“…polymeric matrix with proper filler have shown to have unique properties, due to large surface-area-to-volume ratio of fillers in the polymer matrix, and it is expected that the overall weight of a shield will decrease while its absorption/attenuation abilities improves. Furthermore, this type of material will have higher conformability and lower toxicity comparing to lead [6,8]. In this regard, extensive research has been carried out on the use of metal oxides, such as tungsten trioxide (WO 3 ) as a filler in different polymer matrices, and acceptable results were obtained when applied to gamma and X-ray radiation shields [8-13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, WO 3 обладает полупроводниковыми свойствами [18], что при введении его в диэлектрическую полимерную матрицу позволит значительно снизить или полностью исключить накопление большого электрического заряда при взаимодействии композита с быстрыми электронами в космическом пространстве. Большинство российских и зарубежных работ посвящено в основном изучению радиационнозащитных свойств композитов с WO 3 по отношению к рентгеновскому и гамма-излучению [19][20][21][22]. Работы по оценке радиационно-защитных свойств композитов с WO 3 по отношению к электронному и протонному излучениям немногочисленны.…”
Section: Introductionunclassified